Conflict management in the Mara education institutions, Malaysia - Salleh, Mohamad Johdi; Ramani, Raman (2011)
Conflict if managed appropriately and efficiently would add important values to an organization as it act as a catalyst for change. These changes may lead to a conducive environment in workplace, foster good relationship among employees, and, over a period of time it will result in high productivity. This is important as a team, they can work hand in hand to achieve the organizational goals. Pursuant to this matter, this study attempts to investigate the views of MARA educators on conflict management and identify the processes of managing conflict in the MARA education institutions. The sample of the study was 306 respondents randomly selected from MARA educators who attended the Postgraduate Diploma in Education programme at the International Islamic University Malaysia, Gombak. They were from MRSM, KPM, KKTM, KM and IKM across the country. The data was processed using the Statistical Package for Social Science (SPSS) version 17.0 for Windows. The responses on the questionnaire items were reported and discussed in frequency, percentage, and, mean. The findings shows that the highest score was on ‘Conflict can be thought as problem, we need to find the source and take the appropriate steps to solve it’ with mean score 4.40 of 5.00 Likert scale. The lowest was on ‘It is better to lie a bit in order to solve a conflict’ with mean score 2.51. It is believed that if the educators regardless of background can manage effectively the conflict in schools and foster healthy teacher-administrator relationship, teaching and learning can be improved towards facing the challenges in the era of globalization and realization of vision 2020.